Issues in Islamic Economics, Banking and Financial Institutions during the Covid-19 Pandemic - Azharsyah Ibrahim (Share: Jurnal Ekonomi dan Keuangan Islam, 2021)
In this second issue of the 2021 edition, we received primarily manuscripts focusing on the challenges faced by Islamic Banking and Financial Institutions (IBFIs) during the Covid-19 pandemic. These manuscripts cover a range of topics within the field, including institutional and employee performance, financial stability, waqf institutions, the trend of Islamic economics research, and the significance of Islamic economics and finance in the modern economy. As the publication deadline approached, out of the dozen manuscripts reviewed, only ten were accepted. Nine of them were ready for publication, while the remaining manuscript required further quality improvements. The process involved an initial review by our editor(s) before forwarding the manuscripts to suitable reviewers. Some manuscripts underwent multiple rounds of review before being accepted. The reviewers' feedback played a crucial role in the final decision-making process. Following acceptance, the manuscripts proceeded through editing stages, including proofreading and layout, during which our editor(s) maintained close communication with the authors as necessary. This rigorous process ensures that each published manuscript undergoes thorough quality checks. Notably, among the published articles, five discuss performance issues in Islamic financial institutions, while the others explore various aspects of Islamic economics and finance, including waqf institutions, the trend of Islamic economics research, and the relevance of Islamic economics and finance in the modern economy. For detailed information, please refer to the attached PDF file.